Effectiveness of Flashcard Learning Media Using Canva Application to Enhance Early Reading Skills in First Grade Students - Salsabila; Wahyudi, Urip Muhayat Wiji (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of flashcard media using Canva application in improving the early reading skills of first grade students of SD Negeri 1 Kadipiro. This study used a quasi-experimental method with a non-equivalent pre-test-post-test design. Data collection was done through pre-test and post-test and data recording. The sample of this study was 56 students divided into two classes, namely classes 1A and 1B with the number of students in each class as many as 28 students, class 1A as the control group and class 1B as the experimental group. There was a significant increase in the experimental group's average score from pre-test (61.678) to post-test (83.928). A paired sample t-test showed a significance value of 0.000, indicating a significant difference before and after the treatment. N-Gain analysis showed that flashcard media was more effective than alphabet poster media, with the experimental class having an N-Gain of 58.06 and the control class having an N-Gain of 34.88. This study concluded that flashcards using the Canva application were effective in improving students' early reading skills.